Nanoscopic wear behavior of face centered cubic metals. (1st April 2018) - Ko, H.E.; Park, H.W.; Jiang, J.Z.; Caron, A.
Abstract: The wear behavior of three face centered cubic metals (Au, Ag and Ni) have been investigated by friction force microscopy. Depending on the applied normal load two tribological mechanisms can be distinguished: shearing and ploughing. Our experimental shearing friction data can be well described by the Johnson-Kendal-Roberts model. Our results show a positive correlation between the shear strength and the surface energy of the investigated metals. Further, ploughing is confirmed to be determined by the resistance of a metal to be plastically deformed, i.e. its hardness. We find that the ploughing friction coefficient and the wear volume inversely scale with the hardness. Graphical abstract: Image 1